Papillary thyroid carcinoma presenting as a cystic neck lesion: case series - Subha, Sethu T; Bakri, Mohd- Adzreil; Salleh, Hisyam; Doi, Mohamad; Nordin, Abdul-Jalil (Mashhad University of Medical Sciences, 2018)
Introduction: Papillary thyroid carcinoma (PTC) constitutes 75–85% of all thyroid cancers. PTC usually presents as a subtle, commonly slow-growing, painless thyroid mass or a solitary nodule in the neck. This presentation of a cystic neck lump, without the presence of a thyroid nodule, may imitate the course of a benign disease, thus delaying diagnosis and proper treatment. Case Report: Three cases that had been initially presented as a cystic neck lesion in which a benign etiology was considered primarily were compiled in this study. PTC was only diagnosed after surgical excision of these cystic neck lesions in the first two cases, and after performing fine needle aspiration cytology (FNAC) and an 18fluorine-fluorodeoxyglucose positron emission tomography computed tomography (18F-FDG-PET CT) scan in the latter case. Conclusion: PTC can sometimes present as a cystic neck mass; a presentation which is usually related to a benign lesion. This case series emphasizes that patients who appear to have a solitary cystic neck mass must be treated with a high index of clinical suspicion. Although not a first-line imaging modality, 18F-FDG-PET can be extremely useful in assessing patients with a cystic neck lesion, where diagnosis is still uncertain after standard investigations such as ultrasonography and FNAC have been performed.